Peningkatan Kemampuan Melompat Anak Melalui Permainan Lompat Tali pada Anak Kelompok B di TK Pertiwi 3 Karanganyar - Sumiyati, Sumiyati (Didaktika, 2022)
Jumping is a locomotor movement that makes the body ejected into the air which causes the body to be out of contact with the ground or from the tool and for a moment causes a flying phase. The game of jumping rope is potentially used as a medium. The study aimed to find out the steps to increase children's jumping ability through a game of jumping rope in group B TK Pertiwi 3 Karanganyar. The subjects in this study were children aged 5-6 years at Pertiwi 3 Karanganyar Kindergarten. The total number of children is 15 children, consisting of 7 girls and 8 boys. data collection method in the form of observation sheets and documentation. Based on the empirical data obtained through this research, it shows that before the implementation of the pre-action, the increase was 46.67% with the Start of Development (MB) criteria. After the action was held in cycle I, it increased by 61.67% or with the criteria of Developing According to Expectations (BSH) but these results had not yet reached an indicator of success, namely 80%, for this reason, the researcher held an advanced cycle of cycle II which achieved 80.33% success or with Very Well Developed (BSB) criteria. Therefore, learning the ability to jump through rope jumping games in Group B TK Pertiwi 3 Karanganyar, Sambungmacan District, Sragen Regency was said to be successful and achieved indicators of success in research and the research was stopped